Magnetic quenching of positronium studied by positron annihilation lifetime and Doppler broadening measurements. (June 2020) - Liu, J.D.; Guo, J.Q.; Luo, M.; Wang, Z.; Zhang, H.J.; Ye, B.J.; Chen, Z.Q.
Abstract: Annihilation of positronium (Ps) in static magnetic fields is investigated by positron annihilation lifetime (PAL) and Doppler broadening (DB) measurements of γ-Al2 O3 nanopowder. The properties of four eigenstates of Ps atoms ( | 1, 1 ⟩, | 1, − 1 ⟩, | + ⟩ (long-lived eigenstate mixed from | 1, 0 ⟩ and | 0, 0 ⟩ due to Zeeman effect), and | − ⟩ (short-lived eigenstate mixed from | 1, 0 ⟩ and | 0, 0 ⟩ due to Zeeman effect)) were revealed from PAL and DB results. Thereafter, with magnetic field increasing from 0.105 to 0.760 T, clear and regular variation of Ps annihilation parameters are observed: (1) The mean lifetime of the three long-lived Ps states ( | 1, 1 ⟩, | 1, − 1 ⟩, and | + ⟩ ) shows clear quenching effect; (2) The formation probability of each Ps eigenstate ( | 1, 1 ⟩, | 1, − 1 ⟩, | + ⟩, and | − ⟩ ) keeps unchanged; (3) The intensity of the narrow component (derived from multi-Gaussian fitting) of DB spectrum exhibits a gradual increase which is in good agreement with the theoretical calculation from PAL results (2γ decay of | + ⟩ and | − ⟩ states, and pick-off quenching of long-lived Ps states); (4) The intensity of the low energy region of DB spectrum is diminished by the decrease of 3γ decay of | + ⟩ state. The quantitative correlations between magnetic field and o-Ps annihilation parameters will be helpful for the further understanding of complex Ps quenching effects, such as the effect mixed from orhto-para spin conversion and magnetic quenching. Highlights: Magnetic quenching of positronium was investigated in nanometer-scaled porous γ-Al2 O3 which is very suitable for theformation of positronium. Magnetic quenching of positronium was investigated by using both PAL and DB experimental techniques for the first time. The multi-Gaussian fitting method was utilized to deduce the p-Ps intensity of each sample (the intensity of the narrowest component of each Doppler broadening spectrum).